The Relationship Of Capital Structure To Profitability: Eviden Of Power Companies In G-20 Countries - Feti Puspitasari (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Net Zero Emissions (NZE) have become a major concern for many countries because of their impact on global business and corporate capital structures, especially in the electricity sector. The purpose of this study was to examine the effect of capital structure on profitability. The object of this study is companies in the electricity sector in G-20 countries for 5 (five) years from 2018-2022. The method used in this study was linear regression panel data with observation companies as many as 267 observation data totaling 1,335. The results of this study show that DAR has a negative and significant influence on ROA and ROE in electricity sector companies (electric utilities) in G-20 countries. The findings of this study indicate that companies are better off relying on internal funding first and if the company needs additional funds, it can use the option of issuing new shares.